The Effect of Green Accounting, Environmental Performance, and ESG on SDGs: The Moderating Role of Profitability - Abadiyah, Sa’adatul; Handayani, Mega (E-Jurnal Akuntansi, 2025)
This study aims to examine the effect of green accounting, environmental performance, and ESG on the achievement of SDGs, while also assessing the moderating role of profitability in energy and mining companies in Indonesia. The data were collected from annual and sustainability reports during the 2019–2023 period and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that green accounting, environmental performance, and ESG have a positive and significant effect on SDGs. However, profitability does not moderate the relationship between the three variables and SDGs. These findings suggest that sustainability practices are implemented not merely due to financial strength, but as a response to external pressures and the need for social legitimacy.